Acceptability and Effects of Commercially Available Activity Trackers for Chronic Pain Management Among Older African American Adults. Issue 2 (11th September 2019) - Janevic, Mary R; Shute, Varick; Murphy, Susan L; Piette, John D
Abstract: Background: Wearable activity trackers may facilitate walking for chronic pain management. Objective: We assessed the acceptability of a commercially available tracker and three alternative modes of reporting daily steps among older adults in a low-income, urban community. We examined whether using the tracker (Fitbit Zip TM ) was associated with improvements in functioning and activity. Design: Randomized controlled pilot and feasibility trial. Subjects: Fifty-one African American adults in Detroit, Michigan, aged 60 to 85 years, with chronic musculoskeletal pain (28 in the intervention group, 23 controls). Methods: Participants completed telephone surveys at baseline and eight weeks. Intervention participants wore trackers for six weeks, alternately reporting daily step counts via text messages, automated telephone calls, and syncing (two weeks each). We used multimethods to assess satisfaction with trackers and reporting modalities. Adherence was indicated by the proportion of expected days on which valid step counts were reported. We assessed changes in pain interference, physical function, social participation, walking frequency, and walking duration. Results: More than 90% of participants rated trackers as easy to use, but some had technical or dexterity-related difficulties. Text reporting yielded 79% reporting adherence vs 69% each for automated calls and syncing. Intervention participants did not show greater improvement in functioning or walking than controls. Conclusions: With appropriate support, wearable activity trackers and mHealth reporting for chronic pain self-care are feasible for use by vulnerable older adults. Future research should test whether the effects of trackers on pain-related outcomes can be enhanced by incorporating behavior change strategies and training in evidence-based cognitive-behavioral techniques.